Strategies for New Product Development in an Emerging Market - BASHIR, USMAN; SAEED, SANA; ABBAS, SYED KAZIM (Advances in Social Sciences Research Journal, 2020)
In competitive environment, selection of right strategy for new product development is considered as essential component for any business’s survival. In all available strategies, innovation and competitive strategies are the most important. Many organizations have to face failure while implementing this strategy because of having lack and integration among Research Development., Marketing, Customer and Competitor. This integration is considered the driver for new product development. Accordingly, this study is focusing the importance of right selection within Pakistani context by interviewing key informants working in different organizations. Implications will be beneficial for strategy makers working on new product development